Petrophysical chahracteristic of the granitoids for the estimation of the waste repository objects in the Volyn region of the Ukrainian Shield - TOLSTOI, M.; KUZIV, L.; KOSTENKO, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The question of the disposal the radioactive waste has been studied by a number of researchers. Therefore the estimation of petrophysical suitability of some host rock, which concern the repository of the radioactive waste is very useful. This problem was not under the question before. Taking into account that the direct radioactive waste location nearly the Chornobyl atomic station has paramount value and that granitoids are believed as perspective for radioactive waste repository, this paper describes the most important physical characteristics of penetrability the major granitoids types of the Volyn region of the Ukrainian Shield.